Mechanization of agricultural production in Kenya: Current state and future outlook - Kaumbutho, Pascal; Takeshima, Hiroyuki (International Food Policy Research Institute, 2023)
Agricultural mechanization is the use of machinery, equipment, and implements—rather than human or animal power—to carry out agricultural practices. When the use of mechanization is sufficiently high, it can help improve the overall efficiency of food systems, reduce the costs of producing outputs and providing services, enhance economies of scale, and raise labor productivity and incomes (FAO and AUC 2018; Diao, Takeshima, and Zhang 2020). While mechanized practices are traditionally thought of in terms of tilling, seed drilling, and spraying, in recent years mechanization has been considered to include broader applications along the food system, such as irrigation, postharvest cleaning of harvests, cold storage, value addition, and processing.